Prophylactic training in asymptomatic soccer players with ultrasonographic abnormalities in Achilles and Patellar tendons: The Danish Super League Study - Fredberg, U.; Bolvig, L.; Andersen, N. T. (The American Journal of Sports Medicine, 2008)
A recent study published in The American Journal of Sports Medicine showed that asymptomatic soccer players with an increased risk of developing Achilles and patellar tendon injuries within the next 12 months can be identified with use of ultrasonography.